Makna Tuturan Ritual Marapu Wano sebagai Sistem Nilai Ekologis, Religius, dan Sosial pada Masyarakat Tana Righu di Sumba Barat - Kamuri, Paulus Ama; Malo, Flavianus Mario; Mone, Yohanis Rangga (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study was motivated by an awareness of the meaning and value of local wisdom contained in the Marapu Wano ritual speech, as the true essence of culture is beginning to fade and the younger generation has little knowledge of how to preserve their cultural roots amid technological developments. The purpose of this study is to identify and describe the cultural practices and meanings of Marapu Wano ritual speech in the context of the culture that underlies it. The research method used was descriptive qualitative research. The results of the study show that the Marapu Wano ritual speech contains ecological meanings that reflect the harmonious relationship between humans and nature, religious meanings that affirm the belief system in ancestral spirits and the Creator, social meanings that strengthen solidarity and social order in the community, and meanings of supplication expressed through ritual prayers as a means of conveying hopes for safety, fertility, and prosperity in life. Thus, the Marapu Wano ritual speech can be understood as a cultural value system that plays an important role in maintaining the ecological, spiritual, and social balance of the Tana Righu community in West Sumba.